Kedudukan PT. Angkasa Pura I Dalam Pembayaran Bea Perolehan Hak Atas Tanah Dan Bangunan - Ridwan HR; Nurmalita Ayuningtyas Harahap; Siti Ruhama Mardhatillah (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This paper examines the issues of, first, the special assignment of the Minister of BUMN (State Owned Enterprise) and the Minister of Transportation to PT. Angkasa Pura I (Persero) in land procurement forthe construction of the New Yogyakarta International Airport (NYIA) airport in Kulon Progo Regency, DIY Province whether it can invalidate the obligations of PT. Angkasa Pura I (Persero) to pay BPHTB. Second, it is regarding the land procurement for the construction of the New Yogyakarta International Airport (NYIA) airport in Kulon Progo Regency, Special District of Yogyakarta whether it can be qualified as  "land  acquisition  for  the  development  of  public interest"  which  is  freed  from  the  obligation  to  payBPHTB.  This  is  a  normative  legal  research  using  primary  and  secondary  legal  materials  obtained through literature studies and is analyzed juridical. From the research results, it can be concluded that, first, special assignments could not invalidate the obligations of PT. Angkasa Pura I (Persero) to payBPHTB.  Secondly,  PT.  Angkasa  Pura  I  (Persero)  in  Kulon  Progo  Regency  of  Special  District  of Yogyakarta Province cannot be qualified as "land acquisition for development for public interest" freed from the obligation to pay BPHTB.